Eliminating Disparities in School Discipline: A Framework for Intervention. Issue 1 (March 2017) - Gregory, Anne; Skiba, Russell J.; Mediratta, Kavitha
Race and gender disparities in school discipline and associated harms have been well documented for decades. Suspension from school can reduce instructional time and impede academic progress for students who may already be lagging in their achievement. This chapter offers a research-based framework for increasing equity in school discipline. The framework is composed of ten principles that hold promise for helping educators to address student behavior in a developmentally appropriate manner and reduce race and gender disparities in school discipline. The framework also informs directions for future research in school discipline.